A tale of two ships: the Spanish Civil War reaches the British coast. (February 2014) - Coni, Nicholas
On 2 November 1938 one of General Franco's warships shelled and sank a Spanish merchant ship nine miles from the east coast of England. The captain and his family were rescued by the local lifeboat and the human story, as well as the proximity of the incident to the coast of Great Britain, aroused considerable public interest there. Although not in itself a particularly momentous occurrence in such a destructive war, the sequence of events leading up to the convergence of the two ships on a distant coastline does cast some light on a most neglected aspect of that war—the struggle between the opposing navies to impede the transport of essential supplies to the enemy's ports. It also has ramifications involving naval intelligence, maritime law and the international tensions affecting seafaring nations during the conflict. The political fallout in the UK hinged on the debate as to whether the episode constituted an act of piracy. The subsequent fates of the captain and crew of the sunken ship reflect the ethos of the times. The encounter is most unlikely to have been random and although conspiracy theories are extremely attractive and there is no shortage of candidates, it is unlikely that the identity of the conspirators will ever be known.